Cultural Content Analysis of English Textbook “Bahasa Inggris 2” for Senior High School Grade XI - Iranta Purba, Agnes Dwi; Azkiya, Siti Nurul; Qadri, Asri Nurul; An’asy, Zaharil (TARBIYA: Journal of Education in Muslim Society, 2023)
AbstractThis research aims to discover what and how culture is represented in the "Bahasa Inggris 2" textbook. A qualitative descriptive method was employed in this paper, focusing on documents as the primary data, in which nine chapters were analyzed utilizing a checklist of content analysis. The findings reveal three aspects of culture: cultural categories, elements, and senses. First, following the concept of Cortazzi & Jin (1999), three cultural categories, i.e., source culture, target culture, and international culture, were found in the textbook. Second, cultural elements based on Yuen (2011), i.e., products, persons, perspectives, and practices were observed. Finally, referring to Adaskou et al. (1990), the senses of culture included in the textbook were aesthetic, sociological, semantic, and pragmatic. Concerning the frequency of occurrence, the research results show that the cultural categories were mostly present through source culture (42.75%), whereas the cultural element was dominated by products (48.31%). Lastly, the sociological sense was found to occur the most (44.44%). These findings imply the need to have a balanced representation of the three mentioned cultural aspectAbstrakPenelitian ini bertujuan untuk menemukan apa dan bagaimana budaya direpresentasikan dalam buku ajar “Bahasa Inggris 2”. Metode deskriptif kualitatif digunakan dalam makalah ini, dengan fokus pada dokumen sebagai data primer, sembilan bab dianalisis menggunakan checklist analisis isi. Temuannya mengungkap tiga aspek yang merepresentasikan budaya, yakni kategori budaya, elemen, dan penalaran. Pertama, mengikuti konsep Cortazzi & Jin (1999), tiga kategori budaya, yaitu budaya sumber, budaya target, dam budaya internasional, ditemukan dalam buku ajar. Kedua, elemen budaya berdasarkan Yuen (2011), yaitu produk, orang, perspektif, dan praktik yang diamati. Terakhir, mengikuti Adaskou dkk. (1990), Penalaran budaya yang dimuat dalam buku ajar tersebut bersifat estetis, sosiologis, semantik, dan pragmatis. Dilihat dari frekuensi kemunculannya, hasil penelitian menunjukkan bahwa kategori budaya paling banyak hadir melalui budaya sumber (42,75%), sedangkan unsur budaya didominasi oleh produk (48,31%). Terakhir, penalaran sosiologis ditemukan paling banyak (44,44%). Temuan-temuan ini menyiratkan perlunya representasi yang seimbang dari tiga aspek: kategori budaya, elemen budaya, dan penalaran budaya.